Adolescents Knowledge on Stunting and Its Prevention Efforts as a Strategy for Building a Golden Generation - Salsa Zahra Afiatun Nisa; Heni Heryani (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2026)
Introduction: Stunting remains a major public health problem in Indonesia because it affects physical growth, cognitive development, and the quality of human resources in the future. Stunting prevention efforts should not only focus on pregnant women and children under five but also need to target adolescents as future parents. Adolescents knowledge about stunting, balanced nutrition, anemia prevention, and reproductive health is an important factor in preventing stunting in the next generation. Objective: This study aims to describe adolescents knowledge regarding stunting and its prevention as a strategy for building a healthy and high-quality golden generation. Method: This research used a descriptive quantitative design. The population in this study were junior high school adolescents. The sampling technique used was purposive sampling with a total sample of 31 respondents. Data were collected using a structured questionnaire about adolescents knowledge of stunting and its prevention. Data were presented in the form of frequency distribution tables and analyzed using descriptive analysis. The research instruments used were questionnaires that had been adjusted to the research variables. Result: The results showed that most adolescents had a moderate level of knowledge about stunting and its prevention, with 14 respondents (45%). Meanwhile, 12 respondents (40%) had good knowledge, and 5 respondents (15%) had poor knowledge. These results indicate that adolescents knowledge about stunting prevention is generally adequate but still needs improvement through health education programs. Conclusion: Adolescents knowledge regarding stunting and its prevention is mostly in the moderate category. Improving adolescents knowledge through health education, peer education, and school-based programs is important for stunting prevention and has implications for midwifery practice, especially in promotive and preventive health services for adolescents.